Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Large spatiotemporal variability in CH4 emissions from a subtropical coastal creek in southeast China affected by hydrological and biogeochemical processes - Lihua Wang; Ping Yang; Yingzi Wang; Pingping Guo; Derrick Y.F. Lai; Kwok Pan Chun; Chuan Tong; Dongyao Sun; Jiafang Huang; Guanpeng Chen; Hong Yang (Journal of Hydrology, 2026)

The impact of anti-gout medications on eight cardiovascular diseases: a Mendelian randomized study - Pingping Peng; Jingting Wang; Miaozhen Huang; Congting Hu; Suyan Liu; Jia Liu; Jiaqin Cai; Xiaoxia Wei; Hong Sun (European Journal of Clinical Pharmacology, 2026)

Branch-connected construction of shamrock-shaped giant molecule acceptors enables efficient organic solar cells through optimized molecular architecture - Shanshan Qin; Kangqiao Ma; Jiajia Xi; Fengzhi Wang; Pingping Xi; Hong Huang; Zhenyu Chen; Tao Zhang; Kang Wang; Deping Qian (Chemical Engineering Journal, 2026)

VSIG4 Inhibits Microglia-Mediated Neuroinflammation and Neuronal Injury by Modulating the JAK2-STAT3/NF-κB Signaling Pathway in Parkinson’s Disease - Jingcong Zhuang; Pingping Cai; Zhongjie Chen; Quanlong Hong; Rong Wang; Feng Wang; Yaxin Zhang; Danjie Wu; Fengzhu Chen (Molecular Neurobiology, 2026)

Rapid nitrogen removal in sandy beaches driven by periodic tidal inundations - Lin Wei; Pinghe Cai; Qingquan Hong; Tong Wu; Wei Liu; Yilin Cheng; Pingping Mi (Limnology and Oceanography, 2026)
Sandy beaches are an important passage for the transport of various forms of nitrogen from land to sea. However, export fluxes of these forms of nitrogen and the mechanisms controlling their transformation remain elusive. Using the 224 Ra/ 228 Th disequilibrium approach, we estimated export fluxes of dissolved inorganic carbon and dissolved inorganic nitrogen at three intertidal sandy beaches with distinct slopes along the southeast China's coast. We identified that sandy beaches are a hotspot of nitrogen loss in the coastal ecosystem, with nitrogen removal rates reaching up to 87.1 mmolN m −2 d −1 and removal efficiencies varying between 7% and 82%. Notably, nitrogen removal rates peaked at intermediate seawater percolation fluxes, reflecting the optimal balance of oxygen consumption, marine organic matter remineralization, and nitrate production for fueling denitrification in the beach's interior. In addition, total nitrogen removal increased with beach slopes. This is likely due to the fact that steeper beaches facilitate seawater to percolate more efficiently into the beach's interior and travel along a longer flow path before it drains out, thus allowing denitrification to prevail. Overall, our field observations reveal that instead of the surface “skin circulation,” the “body circulation” system within an intertidal beach governs fluid transport and solute exchange between land and sea. We conclude that intertidal sandy beaches function as an efficient biogeochemical reactor, which attenuates anthropogenic nitrogen inputs to the coastal ocean.

RFAGB model: A new machine learning model for microplastic inversion based on remotely sensed data in Bohai Sea - Ao Shen; Yongzheng Ma; Yuan Li; Pingping Hong; Zhiguang Niu; Ying Zhang; Jingen Xiao; Dianjun Zhang (Water Research, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

A heterogeneous sparsity knowledge guided evolutionary algorithm for sparse large-scale multiobjective optimization - Jing Jiang; Huoyuan Wang; Pingping Tong; Juanjuan Hong; Zhe Liu; Xing Zhuang; Benyue Su; Fei Han (Swarm and Evolutionary Computation, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Metabolic engineering of Kluyveromyces marxianus to produce myo-inositol from starch - Qing Lan; Pingping Wu; Yao Yu; Jungang Zhou; Hong Lu (Bioresource Technology, 2025)

Life‐cycle greenhouse gas emissions associated with nuclear power generation in the United States - Jun Hong Clarence Ng; Pradeep Vyawahare; Pahola Thathiana Benavides; Yu Gan; Pingping Sun; Richard Boardman; Jason Marcinkoski; Amgad Elgowainy (Journal of Industrial Ecology, 2025)
Under the 2022 Inflation Reduction Act, tax credits of up to $3/kgH 2 are available to hydrogen producers if they generate emissions at levels below 0.45 kgCO 2 e/kgH 2 , spurring producers to explore how hydrogen production via electrolysis using electricity generated by nuclear power may qualify for such tax credits. With uranium as a primary fuel for nuclear power plants (NPPs) and no on‐site emissions, the upstream emissions associated with nuclear fuel supply chains largely determine the carbon intensity of nuclear energy. Using the GREET (Greenhouse gases, Regulated Emissions, and Energy use in Technologies) model, we evaluated the life‐cycle greenhouse gas (GHG) emissions of uranium production and the use of uranium to generate electricity in light water reactor (LWR) NPPs. We evaluated the process chemicals and energy inputs throughout the nuclear fuel supply chain to identify the major contributors to nuclear fuel cycle GHG emissions. Such emissions are estimated at 3.0 gCO 2 e/kWh at NPPs in the United States. The greatest share of nuclear fuel cycle GHG emissions—comprising 53% of total emissions—are associated with electricity consumption throughout the fuel supply chain. We extended the analysis to include an evaluation of the carbon intensity of H 2 production via electrolysis using nuclear power from LWRs. Finally, we examined the impact of future (2035 and 2050) electricity supply chain scenarios on nuclear fuel cycle GHG emissions. Our analysis revealed a decrease of 33% (2035) and 46% (2050) in the carbon intensity of nuclear electricity relative to current nuclear fuel cycle GHG emissions.

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

An inversion model of microplastics abundance based on satellite remote sensing: a case study in the Bohai Sea - Pingping Hong; Jingen Xiao; Hongtao Liu; Zhiguang Niu; Yini Ma; Qing Wang; Dianjun Zhang; Yongzheng Ma (Science of The Total Environment, 2024)

Identification and characterization of TMV-induced volatile signals in Nicotiana benthamiana: evidence for JA/ET defense pathway priming in congeneric neighbors via airborne (E)-2-octenal - Yi Hong; Qingxia Zheng; Lingtong Cheng; Pingping Liu; Guoyun Xu; Hui Zhang; Peijian Cao; Huina Zhou (Functional & Integrative Genomics, 2023)
Plants release a mixture of volatile compounds when subjects to environmental stress, allowing them to transmit information to neighboring plants. Here, we find that Nicotiana benthamiana plants infected with tobacco mosaic virus (TMV) induces defense responses in neighboring congeners. Analytical screening of volatiles from N. benthamiana at 7 days post inoculation (dpi) using an optimized SPME–GC–MS method showed that TMV triggers the release of several volatiles, such as (E)-2-octenal, 6-methyl-5-hepten-2-one, and geranylacetone. Exposure to (E)-2-octenal enhances the resistance of N. benthamiana plants to TMV and triggers the immune system with upregulation of pathogenesis-related genes, such as NbPR1a , NbPR1b , NbPR2 , and NbNPR1 , which are related to TMV resistance. Furthermore, (E)-2-octenal upregulates jasmonic acid (JA) that levels up to 400-fold in recipient N. benthamiana plants and significantly affects the expression pattern of key genes in the JA/ET signaling pathway, such as NbMYC2 , NbERF1 , and NbPDF1.2 , while the salicylic acid (SA) level is not significantly affected. Our results show for the first time that the volatile (E)-2-octenal primes the JA/ET pathway and then activates immune responses, ultimately leading to enhanced TMV resistance in adjacent N. benthamiana plants. These findings provide new insights into the role of airborne compounds in virus-induced interplant interactions.

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)